Introduction. Issue 2 (July 2020) - Edmonds, Amanda; Leclercq, Pascale
ABSTRACT: This special issue of the Journal of French Language Studies participates in the 'methodological turn' (Byrnes, 2013 ) in the field of Second Language Acquisition (SLA), by presenting five original articles that focus on different methodological issues in studies on various aspects of the acquisition of French as an additional language. We highlight the contributions of the five articles and situate them within the larger discussion on research methodology. We end by arguing for the need for additional attention to methodology in SLA.